2012
DOI: 10.3844/amjnsp.2012.41.53
|View full text |Cite
|
Sign up to set email alerts
|

SPATIAL DISTRIBUTION OF FIBROBLAST GROWTH FACTOR RECEPTOR 2 IN NORMAL AND LESIONED CENTRAL NERVOUS SYSTEM OF <I>PLEURODELES WALTLII</I>

Abstract: Fibroblast Growth Factors (FGFs) have been implicated in numerous cellular processes including proliferation, migration, differentiation and neuronal survival. One of these growth factors, Fibroblast Growth Factor 2 (FGF2), is apparently implicated in the ability of the adult salamander (Pleurodeles waltlii) to recover locomotion following complete transection of the spinal cord. In a previous study, we reported up regulation of FGF2 during regeneration of damaged axons and recovery of hind limb locomotion. In… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2015
2015
2015
2015

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(5 citation statements)
references
References 43 publications
0
5
0
Order By: Relevance
“…In previous studies (Moftah et al, 2008 , 2012 ), we correlated the recovery of locomotor activity with FGF-2 and FGFR2 mRNAs expression. To investigate the relation between the transcriptional activity of this growth factor and its receptor with neurogenesis, we studied the distribution of FGF-2 and FGFR2 mRNA in the same regions we used for nestin immunohistochemistry, by using in situ hybridization (Figure 5 ).…”
Section: Resultsmentioning
confidence: 98%
See 4 more Smart Citations
“…In previous studies (Moftah et al, 2008 , 2012 ), we correlated the recovery of locomotor activity with FGF-2 and FGFR2 mRNAs expression. To investigate the relation between the transcriptional activity of this growth factor and its receptor with neurogenesis, we studied the distribution of FGF-2 and FGFR2 mRNA in the same regions we used for nestin immunohistochemistry, by using in situ hybridization (Figure 5 ).…”
Section: Resultsmentioning
confidence: 98%
“…It has been recently shown that quiescent ependymoglial cells can be activated to proliferate and regenerate the lost cells after a CNS lesion (Berg et al, 2010 ). As ependymal remodeling occurs, there are interactions between ependymal cells and neurons and, possibly, between ependymal cells and fibrous astrocytes and oligodendrocytes (Chernoff, 1996 ; Moftah et al, 2008 , 2012 ; Fahmy and Moftah, 2010 ).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations